THE RELATIONSHIPS BETWEEN BELIEF, ATTITUDE, SUBJECTIVE NORM, INTENTION, AND BEHAVIOR TOWARDS NUMBERS GAMBLING: THE MALAYSIAN CONTEXT - Ramayah, T; Nasurdin, Aizzat Mohd.; Mohd. Noor, Mohd. Nasser; Beng, Lim Sheng (JURNAL BISNIS STRATEGI, 2002)
The purpose of the study is to determine the relationship between belief, attitude, subjective norm, intention, and behavior towards numbers gambling (legal and illegal) based on the theory of reasoned action (TRA) proposed by Fishbein and Ajzen (1975). Statistical analysis on 198 responses indicates that the TRA could ue used in predicting choice decision of numbers buyers by explaining 58.8 percent of the variance in the intervening variable namely intention to select the operator type. The subjective norm component had a higher predictive power than the attitudinal component. Of the two elements in the normative components, closest friend was found to be more influential.Â  In the corresponding attitudinal components, the more influential elements (in descending order) are convenience, trusted operator, flexible games, and risk.Results of this study indicate that there are about equal number of people who prefer legal and illegal operators. Those in the younger age group are more likely to buy from the illegal operators. Those who prefer the illegal operators buy numbers more often and spend more on bets.